The nuclear weapons dismantlement problem. (November 2014) - Alvarez, Robert
In preparation for the Nuclear Non-Proliferation Treaty (NPT) review conference next year, the United States reports great progress in physically dismantling its nuclear weapons—a foundation for a key pillar of the treaty, which aims, ultimately, to reduce and eventually eliminate the arsenals of the world's nuclear powers. The US Government Accountability Office (GAO), however, presents a very different picture. The US government's statements about nuclear weapons dismantlement "may be misleading, " the GAO concluded in a 2014 report, finding that the National Nuclear Security Administration (NNSA), which oversees dismantlement within the Energy Department, "does not track the actual date that dismantled weapons were retired" and "will not dismantle some weapons retired prior to fiscal year 2009, but will reinstate them, " causing the US nuclear stockpile to grow. Moreover, the Obama administration seeks to cut dismantlement funding and plans to halt dismantlement altogether after 2022, until new and costly nuclear warhead production facilities are established, tentatively in the early 2030s. Until nuclear dismantlement policies are reformed, disposal of unneeded nuclear weapons and their components will continue to be an afterthought, with huge costs looming in the future. Without reform, dismantlement will remain a mismanaged process kept in the shadows, except when it is burnished for display at NPT review conferences.